2022
DOI: 10.1111/cpr.13181
|View full text |Cite
|
Sign up to set email alerts
|

TLR13 contributes to skeletal muscle atrophy by increasing insulin resistance in chronic kidney disease

Abstract: Objectives Insulin resistance in chronic kidney disease (CKD) stimulates muscle wasting, but the molecular processes behind the resistance are undetermined. However, inflammation in skeletal muscle is implicated in the pathogenesis of insulin resistance and cachexia. Toll‐like receptors (TLRs) are known to regulate local innate immune responses, and microarray data have shown that Tlr13 is upregulated in the muscles of mice with CKD, but the relevance is unknown. Materials and Methods We performed in vitro exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In this study, we found that the different manifestations of MUSC differentiation in young and aged states had little to do with the AMPK and PPAR‐α signalling pathways; in contrast, the Wnt and PI3K signalling pathways play an important role in adiponectin signalling pathways and are both involved in modulating muscle and adipose metabolism 40,41 . The activated PI3K signalling pathway can attenuate lipid accumulation, rescues myotube formation and ameliorate skeletal muscle atrophy 42–45 . Wnt signalling participates in the regulation of satellite cell differentiation and self‐renewal, and this pathway is poorly activated in mature skeletal muscles 46 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that the different manifestations of MUSC differentiation in young and aged states had little to do with the AMPK and PPAR‐α signalling pathways; in contrast, the Wnt and PI3K signalling pathways play an important role in adiponectin signalling pathways and are both involved in modulating muscle and adipose metabolism 40,41 . The activated PI3K signalling pathway can attenuate lipid accumulation, rescues myotube formation and ameliorate skeletal muscle atrophy 42–45 . Wnt signalling participates in the regulation of satellite cell differentiation and self‐renewal, and this pathway is poorly activated in mature skeletal muscles 46 .…”
Section: Discussionmentioning
confidence: 92%
“… 40 , 41 The activated PI3K signalling pathway can attenuate lipid accumulation, rescues myotube formation and ameliorate skeletal muscle atrophy. 42 , 43 , 44 , 45 Wnt signalling participates in the regulation of satellite cell differentiation and self‐renewal, and this pathway is poorly activated in mature skeletal muscles. 46 Activated β‐catenin signalling can increase myogenin expression to stimulate myoblast differentiation and inhibit adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle atrophy is a common and serious complication of CKD. Generally, muscle atrophy caused by CKD is attributed to excessive activation of proteolysis pathways [ 133 ]. Potential causes of muscle atrophy in CKD include metabolic acidosis, inflammation, and insulin resistance [ 134 , 135 , 136 ].…”
Section: Relationship Between Inflammation-related Diseases and Skele...mentioning
confidence: 99%
“…Potential causes of muscle atrophy in CKD include metabolic acidosis, inflammation, and insulin resistance [ 134 , 135 , 136 ]. Evidence has suggested that pro-inflammatory factors IL-6, TNF-α, and TLRs can accelerate proteolysis and insulin resistance in CKD [ 133 ]. Overexpression of TLR2 and TLR4 can upregulate IL-6, facilitating muscle atrophy [ 137 ].…”
Section: Relationship Between Inflammation-related Diseases and Skele...mentioning
confidence: 99%
See 1 more Smart Citation